INDIKATOR PELANGGARAN HAK CIPTA LAGU YANG DIGUNAKAN OLEH KONTEN KREATOR YOUTUBE DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Rahmat Dwi Pangestu; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Universitas Pendidikan Ganesha, 2023)
This study aims to determine: (1) law enforcement against perpetrators of criminals acts of babies disposal in the jurisdiction of the Buleleng Regency, (2) Efforts to overcome the occurrence of criminal acts of babies disposal in the jurisdiction of the Buleleng Regency. The location of this research was carried out in Buleleng Regency, namely at the Buleleng Resort Police, State Prosecutor Buleleng, and The Singaraja District Court Class 1B. This type of research is empirical legal research. The sampling technique used in this research is a non-probability sampling technique in a way that used in determining the research subject is the purposive technique sampling. For data processing analysis techniques, using the qualitative research result show that law enforcement against the perpetrators of the crime of illegal logging have gone well, which carried out with the investigation process, the investigator will continue with the arrest, prosecution and execution before a court with refers to Pasal 181 KUHP about Dead Conditions As for the efforts overcoming the occurrence of criminal acts of babies disposal in the jurisdiction of the Buleleng Regency is to instill moral and formally, providing counseling, and enforcing relevant regulations used to the fullest.